Atividade Enzimática da Lacase em Três Fungos Amazônicos Degradadores de Madeira - Silva, Ezequias Andrade da (2006)
Fungi belong to basidiomycete class have been confered efficiency in the biodegradation process of ligninocelullosic materials due to their enzymes. These enzymes have commercial potential that could be utilized to many industrial applications. This paper evaluate the micelial growth and enzymatic activity of laccase of three amazonic white-rot fungi (Pycnoporus sanguineus, FSF7 (Trametes sp) e FSF11 (Trametes sp). Micelial growth was evaluated through the micelial progress in solid media BDA with different concentrations (30, 90, 120 and 300 mcg) of biotin. To enzymatic activity of laccase was used liquid medium (agar-malt) with different concentrations of glucose/ yeast extract, previously autoclaved at 120 C during 15 minutes and pH 6. 5mm of fungi removed from colony edge was used to inoculate in submerged culture under agitation in Sheaker at 180 rpm and 28 C. High (2.5g) and low (25mg) dosage of seryngaldazine was used. After three days of cultivation, the media was filtrated and enzymatic activity determined by XVII spectrophotometer. P. sanguineus had higher micelial growth and FSF11lower at concentration of 120 mcg of biotin. On the whole, biotin in the medium contribute to add micelial growth. Laccase increase when use higt concentration of inductor seryngaldazine. Laccase activity to P. sanguineus increase significantly when higher dosage of seryngaldazine at 3:5 glucose/ yeast extract was used. Hence it follows that vitamin, as for example biotin, contribute to micelial growth more rapid and higher as well as a major concentration of inductor (seryngaldazine) contribute to increase laccase activity.